Scalar Tension and the (Post-)Colonial Anthropocene in Ingrid Winterbach's To Hell with Cronjé. Issue 1 (2nd January 2020) - Premoli, Martin
Abstract : This article argues for the importance of scalar variability in Ingrid Winterbach's novel To Hell with Cronjé (2002). My analysis focuses on the figure of the collection, which appears throughout the novel in two wildly different forms: a written journal and a geologic bedrock. In focusing on these two forms, my article examines how differences in scale shape (and at times disrupt) the hierarchies and narratives communicated by collections, which Susan Stewart defines as constitutive classificatory systems that vanquish temporality and obscure history. My article thus asks (and attempts to answer) the following: in what ways have imperial collections elided and re-ordered alternative perspectives? What marginalised histories might be unearthed by enlarging or shifting the scale of collections? And what reading methodologies might be employed for engaging in this recuperative endeavour? By engaging with these questions, my analysis intervenes in recent critical debates in literary studies concerning the capacity of the novel (and of the realist genre) for handling the complexity and variability of scale. This debate has become especially vibrant in ecocritical discourses and conversations surrounding the Anthropocene, which ask us to consider how the immensity of our current climate crisis upends a teleological, anthropocentric view of history. This article, however, contributes to and complicates this debate by putting it in dialogue with post-colonial and anti-colonial perspectives, which complicate presentist understandings of environmental destruction by insisting on the deeper colonial histories that inform it.